Pengaruh pendekatan model eliciting activities (MEAs) terhadap kemampuan berpikir kritis dan disposisi matematis siswa - Illahi, Kurnia; Pujiastuti, Heni; Samsuri, Samsuri (Jurnal Math Educator Nusantara: Wahana Publikasi Karya Tulis Ilmiah di Bidang Pendidikan Matematika, 2019)
This research is motivated by mathematical critical thinking abilities and low student dispositions, and students are less able to find other alternatives in solving the questions given by the teacher. The purpose of this study is to find out the critical thinking skills of students who get learning using MEAs better than in students who get conventional learning. And to find out the mathematical disposition of students who get learning using MEAs better than students who get conventional learning. This research was conducted at Panimbang 3 Public High School. The sample in this study was class VIII. This research method uses quasi experiments. The instrument used was a critical ability test, and a mathematical disposition scale. The results of this study show that the critical mathematical thinking skills of students who get learning using the Model Eliciting Activities MEAs model are better than students who get conventional learning. And the mathematical Disposition of students who get learning using Model Eliciting Activities MEAs is better than students who get learning conventional.